CDF transcription factors: plant regulators to deal with extreme environmental conditions. (19th February 2020) - Renau-Morata, Begoña; Carrillo, Laura; Dominguez-Figueroa, Jose; Vicente-Carbajosa, Jesús; Molina, Rosa V; Nebauer, Sergio G; Medina, Joaquín
Abstract : Cycling DOF factors are key elements that integrate plant responses to adverse environmental conditions with different aspects of plant growth control and development such as photoperiodic flowering-time or root and shoot growth. Abstract: In terrestrial environments, water and nutrient availabilities and temperature conditions are highly variable, and especially in extreme environments limit survival, growth, and reproduction of plants. To sustain growth and maintain cell integrity under unfavourable environmental conditions, plants have developed a variety of biochemical and physiological mechanisms, orchestrated by a large set of stress-responsive genes and a complex network of transcription factors. Recently, cycling DOF factors (CDFs), a group of plant-specific transcription factors (TFs), were identified as components of the transcriptional regulatory networks involved in the control of abiotic stress responses. The majority of the members of this TF family are activated in response to a wide range of adverse environmental conditions in different plant species. CDFs regulate different aspects of plant growth and development such as photoperiodic flowering-time control and root and shoot growth. While most of the functional characterization of CDFs has been reported in Arabidopsis, recent data suggest that their diverse roles extend to other plant species. In this review, we integrate information related to structure and functions of CDFs in plants, with special emphasis on their role in plant responses to adverse environmental conditions.